(untitled) (International Journal of Pharmaceutical Sciences and Drug Research, 2022)
Cabazitaxel (CTX) is a novel taxane derivative indicated in the treatment of docetaxel-resistant metastatic prostate cancer. However, as with the case of most of the chemotherapeutic agents, CTX suffers from poor physicochemical properties such as low water solubility and dissolution. Current marketed formulation of CTX (sold under brand name ‘JEVTANA’ by Sanofi-Aventis) contains toxic surfactant, polysorbate 80 and organic solvent ethanol to improve its solubility. However, the use of polysorbate 80 as a solubility enhancer causes increased the risk of life threatening hypersensitivity reactions, generalized erythema, hypotension, and bronchospasm. Hence, to avoid the problem associated with this conventional CTX formulation, the nanoparticulate drug delivery system of CTX was developed by employing the QbD approach. Previous study included use of QbD approach to design and optimise nano particulate system of CTX. Multidisciplinary aspects of nanoscience and nanotechnology require broad range of characterization. In fact, quite often a wider characterization of NPs gives idea about its in vivo behaviour as well as its in use stability. The present work emphasizes a “Molecule Centric Approach”, wherein formed nanoparticulate system was evaluated for quantification of drug component, particle size, surface potential, solid state characterization, in vitro drug release study, compatibility study, Photostability study, thermal cycling study reconstitution stability and dilution stability study. Formulation has been characterized and evaluated concerning their performance in in-vivo and their end patient usage. Our in-vitro characterization of nanoparticle formulation provides an indirect indication of good robustness, market acceptance and regulatory acceptance.